Primiparous mothers' perception and expectations regarding social support during the postpartum period: A qualitative study - Foruzan Sharifipour; Mojgan Javadnoori; Zahra Beboodi Moghadam; Mahin Najafian; Bahman Cheraghian; Zahra Abbaspoor (Wolters Kluwer Medknow Publications, 2023)
Background: Social support has been found to positively influence the mothering experience. Yet little is known concerning primiparous mothers' perceptions of social support following childbirth. This qualitative study aims to explore primiparous mothers' perception and expectations regarding social support during the postpartum period. Materials and Methods: This qualitative study with content analysis approach was conducted on 11 postpartum mothers who had been routinely referring to comprehensive health service centers in Kermanshah, Iran, from October 2020 to January 2021 for receiving postpartum care within the first 6 months after birth. Also, to further enrich the study data, interviews were conducted with healthcare providers (n = 6) and husbands (n = 3). Twenty-two semi-structured interviews were conducted individually through a purposive sampling method. Two participants were interviewed twice. Interviews were recorded and transcribed verbatim in Persian and analyzed using conventional content analysis. Results: Three main categories and thirteen subcategories emerged. The main categories were: "comprehensive support", "support barriers," and "support promotion strategies." The main perception and expectation of mothers regarding social support was the sense of not being alone and receiving comprehensive support, especially from the husband and increasing his awareness about this support. Conclusions: An understanding of a comprehensive support, support barriers, and support promotion strategies with respect to social support can help healthcare professionals to develop interventions and programs aimed at promoting mothers' social support in the postpartum period.